Pengaruh Penambahan Etanol Pada Campuran Diesel-Biodiesel Terhadap Penurunan Tekanan Dan Endapan Pada Fuel Filter - Alamsyah, Dava Rizki Nur; Ghurri, Ainul; Wirawan, I Ketut Gede (Teknik Desain Mekanika; Vol 10 No 4 (2022): Oktober 2022 : Teknik Desain Mekanika, 2022)
Abstract Biodiesel is a fuel that has the potential as a substitute for diesel fuel because it is sourced from vegetable oil so that it can be renewed. Biodiesel has the disadvantage that it can shorten the life of the fuel filter because biodiesel has solvent properties so that the dissolved sediment will form deposits on the fuel filter. Ethanol has several advantages, namely it can reduce the value of fuel viscosity and prevent sediment agglomeration. The purpose of this study was to examine the effect of adding ethanol to the diesel-biodiesel mixture on the pressure drop and deposition on the fuel filter. In this study, a test was carried out with 400 liters of fuel flowing through the fuel filter by adding 5% ethanol to the diesel-biodiesel mixture (dexlite, B20 used cooking oil, and B30 used cooking oil). The test is carried out with the initial pressure before entering the fuel filter, which is 105 kPa. The results of this test show that the addition of ethanol to the diesel-biodiesel fuel mixture causes the viscosity of the fuel to decrease and deposits on the fuel filter are reduced. This is shown in the B30 test of used cooking oil + ethanol which produces the largest pressure drop of 45 kPa and when testing dexlite + ethanol produces the smallest pressure drop of 25 kPa. Keywords: Diesel-Biodiesel Blends, Fuel Filter, Ethanol, Pressure Drop